Differential Production of Midkine and Pleiotrophin by Innate APCs upon Stimulation through Nucleic Acid-Sensing TLRs - Elias A. Said; Sumaya Al-Dughaishi; Wadha Al-Hatmi; Iman Al-Reesi; Mohammed S. Al-Balushi; Atika Al-Bimani; Juma Z. Al-Busaidi; Marwa Al-Riyami; Murtadha Al-Khabori; Salam Al-Kindi; Francesco A. Procopio; Shadia Al-Sinawi; et al. (Journal of Immunology Research)
Midkine (MK) and pleiotrophin (PTN) belong to the same family of cytokines. They have similar sequences and functions. Both have important roles in cellular proliferation, tumors, and diseases. They regulate and are expressed by some immune cells. We have recently demonstrated MK production by some human innate antigen-presenting cells (iAPCs), i.e., monocyte-derived dendritic cells (MDDCs) and macrophages stimulated through Toll-like receptor (TLR)-4, and plasmacytoid dendritic cells (pDCs) stimulated through TLR 7. While PTN production was only documented in tissue macrophages. TLRs 3, 7, 8, and 9 are nucleic acid sensing (NAS) TLRs that detect nucleic acids from cell damage and infection and induce iAPC responses. We investigated whether NAS TLRs can induce MK and PTN production by human iAPCs, namely monocytes, macrophages, MDDCs, myeloid dendritic cells (mDCs), and pDCs. Our results demonstrated for the first time that PTN is produced by all iAPCs upon TLR triggering (p<0.01). IAPCs produced more PTN than MK (p<0.01). NAS TLRs and iAPCs had differential abilities to induce the production of MK, which was induced in monocytes and pDCs by all NAS TLRs (p<0.05) and in MDDCs by TLRs 7/8 (p<0.05). TLR4 induced a stronger MK production than NAS TLRs (p≤0.05). Monocytes produced higher levels of PTN after differentiation to macrophages and MDDCs (p<0.05). The production of MK and PTN differs among iAPCs, with a higher production of PTN and a selective induction of MK production by NAS TLR. This highlights the potentially important role of iAPCs in angiogenesis, tumors, infections, and autoimmunity through the differential production of MK and PTN upon TLR triggering.